Effects of an Osteoporosis Prevention Program Based on Health Belief Model Among Females - Jeihooni; Hidarnia; Kaveh; Hajizadeh; Askari (Kashan University of Medical Sciences, 2015)
Background Several studies reported the efficacy of osteoporosis prevention interventions in improvement of people's preventive behaviors. However, there are reports that the interventions were not successful in altering osteoporosis health beliefs and preventive behaviors. Objectives The current study aimed to assess the effect of a program based on health beliefs model (HBM) on females' health beliefs and performances about osteoporosis preventive behaviors. Patients and Methods This quasi-experimental study was conducted on 120 patients registered in two healthcare centers of Fasa, Fars Province, Iran in 2014. A questionnaire including demographic information and HBM constructs was employed to measure the females' beliefs regarding nutrition and walking performance in prevention of osteoporosis bone mineral density (BMD) measured at the lumbar spine and femur before, immediately after the intervention, and six months after the intervention. Data were analyzed using Chi-square, independent samples t-, Mann-Whitney U tests and repeated measures ANOVA. Results Immediately and six months after the intervention, a significant increase was found in the intervention group's health beliefs, nutrition, and walking performances to prevent osteoporosis. Six months after the intervention, lumbar spine BMD T-score increased to 0.127 ± 0.061 in the intervention group but reduced to -0.043 ± 0.059 in the control group. Also, hip BMD T-score increased to 0.125 ± 0.088 in the intervention group, but decreased to -0.028 ± 0.052 in control group. Conclusions The current study showed the effectiveness of HBM in adoption of nutrition and walking behaviors as well as the increase of bone density to prevent osteoporosis.